Como fazer o rastreamento de agendas político-institucionais? Teoria, metodologia e técnicas de pesquisa para prospectar eventos futuros e antecipar seu impacto na agenda de políticas públicas - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– Contrary to the famous saying, "In Brazil, even the past is uncertain", we can demonstrate that the future, at least in the short term, is quite predictable. This Discussion Paper presents the framework for agenda-setting anticipation through methodologies of actor mapping and agenda tracking, as well as web mining, and information scanning techniques. The paper aims to lay the foundation for a series of studies designed to anticipate the agenda and events on the political-institutional calendar of the Brazilian state in 2024. We hope more people have the opportunity to be alert to what is forthcoming and to organize themselves to engage in debate and influence decisions. They can also more clearly perceive how certain crucial agenda issues remain stalled and completely forgotten of any state deliberation, thereby obstructing the possibility of their institutionalization as public policy.
Keywords: H11; Z18; D72; H83; 330; agenda-setting; actor mapping; policy analysis; web mining; information scanning; 2024